Feature Extraction on Medical Image using 2D Gabor Filter - Zainudin, Muhammad Noorazlan Shah; Mohd Said, Muzalifah; Ismail, Mohd Muzafar (Scientific.Net, 2011)

(untitled)
Mammography is a specific type of imaging that produces an X-ray picture of the human breast. Detection of tumors at an early stage is important step in diagnosis of the abnormalities in mammograms. In many of the cases, preprocessing process of the raw image involving of enhancement, filtering and determination of textural features have been necessary for successful implementation of this study. Raw image is applied histogram equalization method in order to enhance the image intensity. Thus, the noise of that image is eliminated using Gaussian filtering method. Gabor wavelet based algorithm such Gabor filter is used to extract the feature of that images.